The unpredictable body, identity, and disclosure: Identifying the strategies of chronically ill students at university - Toller, Louise; Farrimond, Hannah (Disability Studies Quarterly, 2021)
The experiences of university students with chronic illnesses have been neglected in previous research, despite the fact that they make up the third largest disability category in the UK. The propensity of chronic illnesses to fluctuate unpredictably sets them apart from other forms of disability, yet little is known about how this inherent uncertainty impacts experiences in higher education, or the strategies students develop in order to simultaneously manage their illness and studies. This article presents a thematic analysis of episodic interviews with 13 current or recent UK university students with chronic illness. One student (Sophia)'s narrative is used as a case study through which the main themes are illustrated, with the stories of other students woven around this, building up a picture of uncertainty and unpredictability. The ill body was consistently experienced as a frustrating barrier around which life had to be reshaped. Utilising university disability support required disclosure and the acceptance of a disabled identity, yet also minimised the intrusion of illness by enabling students to work within their limitations, reducing the risk of symptom exacerbation or relapse. While participants did not struggle to be accepted as disabled or to access support, the fluctuating nature of their chronic illnesses failed to fit the narrower conceptualisations of disability that institutional systems were often created for. Participants felt that the support systems provided were not designed for liminal conditions, that standard support and adjustments were not always relevant to their needs, and that provision was inconsistent. In conclusion, this mismatch between the needs of chronically ill students and support provision demonstrates that gaps between equality policy and practice exist in UK higher education institutions.